Strategic Function of Islamic School Principals in Combating Bullying Through the Promotion of Islamic Values - Supriyadi, Ahmad; Suminto, Suminto; Rafikasari, Elok Fitriani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This research aimed to examine the strategic function of Islamic school principals in combating bullying through the promotion of fundamental values. Method: A sequential explanatory mixed-method was used to collect quantitative data from 192 junior high school students at SMP Islam Tahfidzul Quran Sunan Gunung Jati to evaluate knowledge and conduct about bullying. The next step included qualitative interviews with school principal to investigate value-based solutions. Results: The results showed that students had a profound conceptual knowledge of the detrimental nature and manifestations of bullying, specifically in the physical and verbal forms. Behavioral data reported a continued prevalence of verbal and relational bullying, including name-calling and social exclusion, despite students' recognition of the detrimental effects. Qualitative results suggested that school principal actively incorporated Islamic teachings, such as adab (etiquette), ukhuwah islamiyah (Islamic brotherhood), and amar ma’ruf nahi munkar (enjoining good and prohibiting wrong) into school activities to cultivate ethical behavior among pupils. Novelty: This comprised religious instruction, counseling, character development activities, and peer ambassador initiatives. The research showed that successful anti-bullying initiatives must be extended beyond awareness by improving moral consciousness through values-based leadership. Despite being confined to a single Islamic educational context, the results presented a reproducible framework for institutions. Future research should include various educational institutions and evaluate the enduring effects of values-based treatments. The incorporation of Islamic ideals into educational culture was essential for cultivating respectful, nonviolent learning environments.